Overcoming the Impact of Online Games through Literacy for Junior High School Students in South Tangerang City - Said Romadlan; Mukhlis Muhammad Maududi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: A form of communication technology widely played today is an online game, which is a type of game that utilizes computer networks. However, this type of game can cause addictive effects in the long run, such as in the case of Islamic Junior High School students Raudlatul Hikmah, thereby leading to decreased learning performance. This research aims to provide online game literacy training, such as the development, characteristics, and forms of online gaming, regulation, ethics, and the effects of online games, and tips on overcoming them. Contribution: This research contributes to students' understanding of the development characteristics and forms of online games, as well as the regulations, ethics, and their effects, to overcome its negative impacts. Method: Methods applied include sharing experiences in using online games, presentations and discussions on its literacy, and  questionnaire and guided group discussions on online game problems. Results: The results showed that on the average, 82% of students understand the development, characteristics, and types of online games. Meanwhile, 96% understand its effects, while 85% have adequate knowledge of the tips needed to overcome the associated adverse effects. Conclusion: In conclusion, the objectives set by this training program can meet the target of providing online game literacy for Islamic Junior High School students Raudlatul Hikmah